(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
Nigeria is today faced with numerous challenges in its attempt to fulfil its increasing energy demands. This paper seeks to examine the opportunities that coal as an energy resource presents, particularly for a developing country like Nigeria. The purpose of this study is to carry out an exhaustive geochemical analysis of selected Awhum coals from the African Pit and Quarry site with particular emphasis on their suitability for energy production and their attendant economic and social impact on the environment. To accomplish this, both ultimate and proximate analyses were conducted on the coal sample which were sourced from Awhum site. The accumulation of coal with a high level of carbon and hydrogen was estimated; nitrogen, sulfur and oxygen were estimated to be low. In particular, nitrogen and sulfur amount were defined as 1.07%wt and 0.39%wt respectively. The proximate analysis results gave moisture content of 4.40wt.%, volatile matter of 51.16wt.%, fixed carbon of 40.63wt.% while the ash content was 3.81wt.% which all reflect the potential of the produced energy. APQ coal has an HHV of 23.74 MJ/kg, this is due to the low carbon (C), hydrogen (H) and high oxygen (O) content in APQ. Based on the ASTM D388 standard, the coals were classified as Sub-bituminous (Black) low-rank coals (LRCs) with an impressive potential for energy recovery. The properties of this coal make it suitable for industrial and domestic heating, and electric power generation, coke blending or co-firing with biomass for energy recovery through pyrolysis, gasification or combustion.